DETEKSI PARASIT MALARIA PADA DARAH DONOR DI PALANG MERAH INDONESIA KABUPATEN PELALAWAN - Ary Anggi Kristiana; Suri Dwi Lesmana; Fatmawati " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Blood transfusion can be a life saving action but can transmit several blood borne infections, one of them is malaria. Frequency of malaria by blood transfusion was increased in endemic area. Pelalawan regency is an endemic area with high risk transmission of malaria by blood transfusion. This is a descriptive research with cross sectional approach to detect malaria parasites in blood donors. Samples were blood donors in Indonesian Red Cross Society of Pelalawan regency. Samples were taken on scheduled donation with simple random sampling technique. Malaria antigent was detected by Inostics malaria test kit and Giemsa staining thick and thin blood smear for microscopic examination. There were 45 blood donors samples. Samples characteristic was consist of A blood type is 14 samples (31,1%), O blood type is 14 samples (31,1%), B blood type is 13 samples (28,9%) and 4 samples (8,9%) is AB blood type. The donors were between 20 to 52 years old. There was 41 male donors and the remaining were 4 female. All of donors from Pelalawan regency with majority of donors (23 people) from Pangkalan kuras district. This research showed malaria parasites and malaria antigent are not found in all samples and frequency of malaria based on species in blood donors was 0 (0%).Key words : blood donors, transfusion related infection, malaria, malaria antigent detection, malaria microscopic